The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.14506/ca31.4.06
|View full text |Cite
|
Sign up to set email alerts
|

The Blue Years: An Ethnography of a Prison Archive

Abstract: This article is an ethnographic account of an archive of prison letters written by three generations of female kin. Based on long‐term ethnographic research in rural New Mexico, it describes the context in which the letters were written, as well as the desires, preoccupations, and practices that transformed them into an archive. I have placed a particular focus on how dislocation and connection manifest in the letters and shape the kinds of narratives the archive tells. Themes of isolation, loss, and memory ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 25 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…And so I returned to a project that I thought was finished. “The people and places that we circle back to in the ethnographic endeavor—hence in space, time, and writing—are critical practices integral to the making of new forms of knowledge,” wrote Angela Garcia (, 588).…”
mentioning
confidence: 99%
“…And so I returned to a project that I thought was finished. “The people and places that we circle back to in the ethnographic endeavor—hence in space, time, and writing—are critical practices integral to the making of new forms of knowledge,” wrote Angela Garcia (, 588).…”
mentioning
confidence: 99%
“…On the shelf behind me is a row of more binders filled with archival letters that were either bequeathed to me by interlocutors or copies of letters that I have found in archives. Far from inert artifacts of the past, these letters are materialized experience, consciousness, affect, and social life (Garcia 2016(Garcia , 2020Luk 2018).…”
Section: Epistolary Methods Social Death and Black Masculine Care As Rebellionmentioning
confidence: 99%
“…Anthropologists and other social scientists have increasingly drawn on letters as sources of ethnographic material (Garcia 2016(Garcia , 2020Kohn 2012;Ralph 2020;Uzwiak and Bowles 2021). As a data-gathering strategy, Jennifer Harris (2008, 8) has found that correspondence is effective at eliciting intensely personal conversations that would be less likely to occur through traditional interviewing techniques.…”
Section: Epistolary Methods Social Death and Black Masculine Care As Rebellionmentioning
confidence: 99%
“…Nevertheless, my argument here does not steer toward a final account of exclusion. The archive, writes Garcia, may “open up the possibility of new historical narratives and modes of subjectivity” (2016: 575). Exploring daily life in the unit, I investigated how Sory and his coworkers were able to tell their own stories through alternative mediums and in intimate circles, and notably through what I would describe as private archives: recorded interviews, pictures and private movies, together with material memories from the unit that represented for them proofs of their involvement (see Photo 4).…”
Section: A Visit To An Old Friendmentioning
confidence: 99%